The status of Hormathophylla baetica: a new combination and lectotypification in Hormathophylla cochleata - Salmerón-Sánchez, Esteban; Aguilar, Javier Fuertes; Španiel, Stanislav; Mendoza-Fernández, Antonio Jesús; Martínez-Hernández, Fabián; Mota, Juan F. (Phytotaxa, 2016)
The taxonomic status of Hormathophylla baetica and its phylogenetic relationships to other Hormatophylla species are the subject of controversy. As part of an ongoing study on the genus Hormathophylla, we find that molecular, morphological and biogeographical evidence supports the placement of H. baetica as a subspecies of H. cochleata. We also discuss and designate a lectotype for H. cochleata.